Forage germplasm distribution by ILCA - Hanson, Jean (Australian Centre for International Agricultural Research, 1990)
ILCA adheres to the CGIAR policy on germplasm distribution and provides germplasm from its active colleciton free of charge to any bonafide forage worker. The selection of germplasm, preparation and distribution methods in use by the Forage Genetic Resources Unit at ILCA are discused.